Relationship between Myopia Progression and School Entrance Age: A 2.5-Year Longitudinal Study - Linjie Liu; Dandan Jiang; Chunchun Li; Yaoyao Lin; Wenzhe Zhou; Haishao Xiao; Yanyan Chen (Journal of Ophthalmology)
Objective. To investigate the association between myopia progression and school entrance age among Chinese schoolchildren and to suggest a more appropriate school age. Methods. 1,463 children aged six to nine years from Wenzhou, China, were examined and followed up for two and a half consecutive years. Their noncycloplegic refraction was measured twice each year by using an automatic refractometer; axial length (AL) and corneal radius of curvature (CRC) were tested annually by using the IOLMaster for 2.5 years. The questionnaires were completed by the children to collect detailed information regarding risk factors. Here, myopia is defined as a spherical equivalent less than −1.0D. Results. The changes in spherical equivalent (SE) of 7-year-old children in grade 1 and grade 2 were −0.45D and -0.56D, while changes in AL were 0.59 mm and 0.62 mm, respectively. The SE changes of 8-year-old children in grade 2 and grade 3 were −0.54D and −0.75D; meanwhile, the AL changes were 0.57 mm and 0.61 mm, respectively. Significant statistical differences were observed in ocular biological structure parameters, except for corneal radius of curvature (CRC) or anterior chamber depth (ACD), among children with the same age in different grades during this study. The prevalence of myopia was also significantly higher in higher grades for children with same age. Conclusions. Myopia is related to children’s school entrance age. Children who start school in an earlier age are more likely to suffer from myopia, and the progression of myopia can be considerably faster. Therefore, it is recommended to enter school after the age of 7.